QUEUE BUSY PERIOD LENGTH WITH PME DISTRIBUTION ANALYSIS THROUGH LAPLACE TRANSFORM - Ferreira, Manuel Alberto M. (Acta Scientiae et Intellectus, 2024)
In this article it is shown that if the busy period of a queue system is PME distributed, the respective service time is a random variable with a long-tail distribution. The result is obtained through Laplace transforms analysis.